Safety and Prognosis in Percutaneous vs Surgical Tracheostomy in 27 Patients With COVID-19. (September 2020) - Riestra-Ayora, Juan; Yanes-Diaz, Joaquin; Penuelas, Oscar; Molina-Quiros, Cristina; Sanz-Fernández, Ricardo; Martin-Sanz, Eduardo
During the SARS-CoV-2 pandemic, patients in intensive care units who are undergoing long-term intubation may require tracheostomy. There is controversy about indication and health care professionals' safety regarding the conventional or percutaneous technique. We performed a prospective analysis of a series of 27 consecutive patients with COVID-19 comparing both tracheostomy techniques, safety, and prognosis clinical markers. The results show that the techniques are equally safe, without cases of infection in surgeons. The Sequential Organ Failure Assessment score before surgery and the progression in ventilation support during the first 72 hours after tracheostomy are optimal prognostic markers for these patients.